020 Long-term efficacy of ocrelizumab in relapsing multiple sclerosis: 6 study years. Issue 6 (27th May 2022) - Giovannoni, Gavin; Kappos, Ludwig; Seze, Jerome de; Hauser, Stephen L; Overell, James; Koendgen, Harold; Prajapati, Kalpesh; Manfrini, Marianna; Wang, Qing; Wolinsky, Jerry S
Abstract : Background: Efficacy/safety of ocrelizumab in relapsing multiple sclerosis were demonstrated in the OPERA I/II (NCT01247324 /NCT01412333) double-blind period (DBP). We assessed the efficacy of switching to or maintaining ocrelizumab after 4 years of the open-label extension (OLE). Methods: At OLE commencement, patients continued ocrelizumab (OCR-OCR) or switched from interferon-β-1a to OCR (IFN-OCR). Adjusted annualised relapse rate (ARR), time-to-onset of 24-week confirmed disability progression (CDP24) and risk of requiring a walking aid (Expanded Disability Status Scale score ≥6.0) from DBP baseline were analysed. Results: Among IFN-OCR switchers, ARR decreased year-on-year from 0.2 in the pre-switch year to 0.04 in OLE Year 4; OCR-OCR continuers maintained low ARRs (pre-switch, 0.13; OLE Year 4, 0.05). CDP24 was lower year-on-year in OCR-OCR continuers versus IFN-OCR switchers in the pre-switch year (7.7% vs 12.0%) and at OLE Year 4 (19.2% vs 23.7%); p<0.05 all comparisons. Over the DBP and OLE, risk of requiring a walking aid was 44% lower (p=0.004) in OCR-OCR continuers versus IFN-OCR switchers. Conclusions: After 6 years of follow-up, rates of patients with CDP24 and risk of requiring a walking aid remained lower in earlier initiators of ocrelizumab (OCR-OCR) versus those initially receiving IFN (IFN-OCR), demonstrating maintained benefits of earlier treatment with ocrelizumab. g.giovannoni@qmul.ac.uk